Inactivation of Staphylococcus aureus in raw salmon with supercritical CO2 using experimental design - CUPPINI,Mônica (2016)
Abstract Considering the microbial safety of consumption of raw foods (Asian food), this study aimed to explore the inactivation S. aureus in raw salmon by supercritical CO2 treatment (SC-CO2). For this purpose, experimental design methodology was employed as a tool to evaluate the effects of pressure (120-220 bar), the depressurization rate (10 to 100 bar.min–1) and the salmon:CO2 mass relation (1:0.2 to 1:1.0). It was observed that the pressure and the depressurization rate was statistically significant, i.e. the higher the system pressure and depressurization rate, the greater the microbial inactivation. The salmon: CO2 mass relation did not influence the S. aureus inactivation in raw salmon. There was a total reduction in S. aureus with 225 bar, a depressurizing rate of 100 bar.min–1, a salmon: CO2 mass relation of 1:0.6, for 2 hours at 33 °C.